2009
DOI: 10.1111/j.1365-2656.2009.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence and climate effects in Rocky Mountain elk: an application of regression with instrumental variables for population time series with sampling error

Abstract: Summary 1.  Sampling error in annual estimates of population size creates two widely recognized problems for the analysis of population growth. First, if sampling error is mistakenly treated as process error, one obtains inflated estimates of the variation in true population trajectories (Staples, Taper & Dennis 2004). Second, treating sampling error as process error is thought to overestimate the importance of density dependence in population growth (Viljugrein et al. 2005; Dennis et al. 2006). 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 36 publications
(65 reference statements)
2
36
0
Order By: Relevance
“…Climate change can affect aspen survival directly through impacting sucker survival, and indirectly by altering the strength of herbivory (figure 3a), but can also affect herbivore abundance. Indeed, though the elk population in northern Yellowstone itself has declined since the late 1990s [33], elk populations in many other localities in the Rocky Mountains are predicted to increase [13,34] owing to reduced winter snowpack across much of the western United States [35]. Thus, across the northern Rocky Mountain region, aspen recruitment could be precluded owing to more intense herbivory combined with changed abiotic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change can affect aspen survival directly through impacting sucker survival, and indirectly by altering the strength of herbivory (figure 3a), but can also affect herbivore abundance. Indeed, though the elk population in northern Yellowstone itself has declined since the late 1990s [33], elk populations in many other localities in the Rocky Mountains are predicted to increase [13,34] owing to reduced winter snowpack across much of the western United States [35]. Thus, across the northern Rocky Mountain region, aspen recruitment could be precluded owing to more intense herbivory combined with changed abiotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is an ecologically important tree species [14] that is in widespread decline across much of the US northern Rocky Mountains [15] owing to recruitment failure in the face of intense elk herbivory [16], possibly in combination with climatic factors [15]. Indeed, aspen demography is affected directly by both climate [17,18] and elk herbivory [16], while elk themselves may be affected by climate change-altered snowpack conditions [13]. Elk browse on woody shrubs in the winter while during the growing season they are grazers.…”
Section: Introductionmentioning
confidence: 99%
“…While declining snowpacks may have implications for plant communities and patterns of streamflow, they may also influence elk populations. For example, Creel and Creel (2009) found that the steady growth of Montana elk populations in recent decades was inversely correlated with declining snowpacks. When they coupled their analysis with regional predictions of global climate change over the next 20-50 years, results indicated increased elk population growth rates were likely if snowpack amounts continue to decline as predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Elk cope poorly with deep snow and severe winter weather (Creel & Creel, 2009, Hebblewhite et al, 2002, and in Jasper, severe winter weather did cause two elk population crashes. The crash of the late 1940s occurred during an era of intense predator control, and the elk population subsequently recovered.…”
Section: Number Of Elk Killed Number Of Elkmentioning
confidence: 99%
“…In particular, we weighed the evidence to discriminate among three general hypotheses of caribou decline in Jasper National Park: climate change, human disturbance, and wildlife management. The hypothesis of caribou decline due to climate change is that warmer temperatures and shallower snow should favour elk (Creel & Creel, 2009, Hebblewhite et al, 2002 to the detriment of caribou via apparent competition. The hypothesis of caribou decline due to human disturbance is that large numbers of people using wilderness areas can displace caribou from important habitat, thus causing population decline.…”
Section: Introductionmentioning
confidence: 99%